Comparison of intrusion detection system based on feature extraction - Laxkar, Pradeep; Chakrabarti, Prasun (International Journal of Engineering and Technology, 2018)
In network traffic classification redundant feature and irrelevant features in data create problems. All such types of features time-consuming make slow the process of classification and also affect a classifier to calculate accurate decisions such type of problem caused especially when we deal with big data. In this paper, we compare our proposed algorithm with the other IDS algorithm.Â Â